DIABETES MELLITUS RELATED KNOWLEDGE AND AWARENESS - A SURVEY AMONG DENTAL STUDENTS - B, Amrithaa.; Ganesh S, Balaji; R., V. Geetha (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: Diabetes mellitus is a metabolic disorder, which is a high-risk factor for periodontal disease. Diabetes mellitus and periodontal disease show a bidirectional relationship. Oral health professionals to treat asymptomatic patients with undiagnosed diabetes mellitus. Diabetes mellitus is characterized by polyuria, polydipsia, and weight loss. Diabetes will cause delayed wound healing. Management of diabetes mellitus is to delay microvascular and macrovascular complications. Aim: To study the knowledge and awareness of diabetes mellitus among dental students. Material and Method: A questionnaire-based study was conducted among 310 students of Saveetha Dental College, Chennai. Results and Discussion: The obtained results showed that dental students are aware but still have to gain some knowledge about diabetes mellitus. 89.4% say to check blood sugar level before any dental surgical procedure. Only 3.9% were aware of the HbA1C blood investigation. 72.9% say that there is a bidirectional relationship between DM and periodontitis. 65.8% of dental students were aware of symptoms of diabetes mellitus. Conclusion: Within the limitations of the study, we can conclude that there is an adequate level of awareness about diabetes mellitus among dental students. The dental students lack knowledge about the risk factors associated with diabetes mellitus, such as obesity, and they are not aware of certain blood investigations for diabetes mellitus, such as HbA1C.